Psychological Disorders in Primary Care: Cross-Cultural Comparisons - Reeler, Anthony P (PINS-Psychology in Society, 2026)
Epidemiological investigations of psychological disorder have had a strong boost in the past decade by the adoption of new methods of epidemiological investigation. The adoption of definitional approaches to the study of psychopathology has clearly demonstrated the high prevalence of psychological disorders, and particularly the high rates of psychological disorder among primary care patients (Goldberg & Huxley, 1980). This general finding has been commented upon in various reviews, with one of the most recent reviews arguing for an increasing focus upon primary care (Shepherd & Wilkinson, 1988). The high prevalence of psychological disorders in primary care settings has also been shown in many different cultures, which is supportive of the general model developed by Goldberg and Huxley (1980). Cross-cultural comparison has often been a method for establishing the limits of models, and the present paper examines the findings from epidemiology in order to indicate the limitations of the Goldberg model.